Situação dos leitos neonatais em maternidades brasileiras: uma análise exploratória - MIRANDA, Elaine Cristina Silva (2020)
Neonatal units in Brazil should be organized as a progressive care line with intensive care beds and intermediate care beds, with two types: conventional and kangaroo, as recommended by Ordinance 930/2012 of the Ministry of Health. The definition of two typologies for intermediate care is a consequence of the alignment of the actions of Rede Cegonha with the successful Brazilian experience with the implementation of the Humanized Care of the Low-Weight Newborn - Kangaroo Method (MC). The aim of this study is to evaluate the situation and adequacy of neonatal beds in institutions linked to the Stork Network. Descriptive study conducted in 606 maternity hospitals located in all regions of Brazil. The databases used were from the national survey of “Evaluation of Good Practices in Childbirth Care and Delivery at Stork Network Maternities” and the National Live Birth System (SINASC). To calculate and evaluate the distribution of neonatal beds, the parameters proposed by the Ministry of Health through Ordinance 930/2012 were used, which considers that for each 1000 live births there is a need for 1 intermediate kangaroo care bed, 2 intensive beds and 2 conventional care beds. Data were presented as absolute and relative frequency. The minority of neonatal units (24.42%) is organized as a progressive care line with the three planned bed types. Kangaroo intermediate care beds are the minority of implanted beds (11.27%). There is a concentration of intensive and intermediate beds in the Southeast and South regions that present intermediate kangaroo care bed deficit (7.49% and 7.37% respectively). By analyzing the adequacy of beds by the number of live births, there is inadequacy of Kangaroo intermediate care beds in all regions of Brazil, intensive bed deficit in the North and Northeast, and adequacy of conventional intermediate care beds in all regions. . There is a lack of equity in the distribution of technological resources and the implementation of Kangaroo intermediate care beds in Brazil is still incipient. There is a failure to implement public policies based on scientific evidence. Greater efforts are required to implement progressive care and reduce regional differences.